Fabrication and Evaluation of Sustained Release Mucoadhesive Losartan Potassium Matrix Tablets - Mukul, Md Emdadul Hasan; Ahmed, Sayed Koushik; Akter, Mariyum; Hossain, Mohammad Salim (Bangladesh Pharmaceutical Journal, 2015)
Sustained release matrix tablets of Losartan potassium were prepared with different types of mucoadhesive polymers e.g. Hydroxypropylmethyl cellulose (HPMC), Sodium carboxymethyl cellulose (Na-CMC) and Methyl cellulose (MC). The tablets were prepared by direct compression method and then were subjected to in-vitro drug dissolution for 8 hours in phosphate buffer of pH 6.8. The mucoadhesive property was investigated in terms of retention time by wash-off method. Irrespective of amount of polymer, mucoadhesive strength of MC was proved to be maximum where HPMC and Na-CMC showed moderate or poor mucoadhesive strength. Drug release from all formulations followed Higuchi release mechanism. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22297 Bangladesh Pharmaceutical Journal 16(2): 153-157, 2013